2016
DOI: 10.5539/ass.v12n4p179
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of Mindfulness-Based Stress Reduction on Intolerance of Uncertainty and Anxiety Sensitivity among Individuals with Generalized Anxiety Disorder

Abstract: <p class="a"><span lang="EN-US">The Generalized Anxiety Disorder (GAD) is one of the most chronic and detrimental disorders and it is considered a common disorder in childhood and adolescence. Furthermore, this disorder is associated with many problems in the health domain. As such, this study attempted to gauge the impact of mindfulness-based stress reduction on intolerance of uncertainty and anxiety sensitivity among students with generalized anxiety disorder. Therefore, it was attempted to run a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 41 publications
2
14
0
1
Order By: Relevance
“…This corroborates previous findings where higher levels of mindfulness, whether defined as a trait or skill that can be cultivated, mean fewer mental health problems [22]. Furthermore, Alimehdi et al [16] found that mindfulness-based stress reduction programs decreased the symptoms of GAP, but also IU and anxiety sensitivity, its two key components. The relevance of mindfulness in overall well-being is clearly supported by prior studies, but also with current research.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This corroborates previous findings where higher levels of mindfulness, whether defined as a trait or skill that can be cultivated, mean fewer mental health problems [22]. Furthermore, Alimehdi et al [16] found that mindfulness-based stress reduction programs decreased the symptoms of GAP, but also IU and anxiety sensitivity, its two key components. The relevance of mindfulness in overall well-being is clearly supported by prior studies, but also with current research.…”
Section: Discussionsupporting
confidence: 89%
“…One construct that emerged as one of the protective factors for the development of many psychological disorders, and is extensively examined in recent studies, is mindfulness [16,17]. Commonly defined as the state of attention and awareness in the present moment, it found its way into the western world, although it is rooted in the teachings of Buddha [18].…”
Section: Mindfulness As a Protective Factormentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning the effectiveness of MBSR on IU in this group, the current research results suggested no effects of the provided treatment on IU in the investigated participants. This finding was consistent with those of previous research [22]. However, they were inconsistent with the results of Vered Miriam [23] and Lee [24].…”
Section: Discussionsupporting
confidence: 71%
“…Furthermore, clinical observations highlighted that IU plays an essential role in increasing worry and rumination [21]. Concerning the effectiveness of MBSR on IU in this group, the current research results suggested no effects of the provided treatment on IU in the investigated participants.…”
Section: Discussionmentioning
confidence: 53%